Achieving high performance anticorrosive nanosheet photo-catalysts via a metal, surfactant co-modification approach. (October 2021) - Yu, Liang; Wang, Yu; Xia, Xiaohong; Chen, Xuxing; Huang, Zhongbing; Homewood, Kevin Peter; Gao, Yun
Highlights: We showed the photo-corrosion process of TiO2 nanosheet. Facile photo-deposition method in aqueous solution was used. TiO2 -Au-4h(PVP) displayed the highest QE of 30.9 % and best stability. This method can be generally valid for other nanosheet photocatalyst. Abstract: Though TiO2 was famous for good chemical stability, as an ultrathin flaky structure, TiO2 nanosheet also got mired in photo-corrosion. Herein, we explored the inner mechanism of photo-corrosion phenomenon among nanosheet structure, and demonstrated the vital role of high specific surface area and perfect dispersity of nanosheet photo-catalyst in H2 evolution reaction, rather than the heterophase junction of TiO2 (B)/λ-Ti3 O5 . Through exploring four different Conditions, we have confirmed the important modification of highly active metal co-catalyst and surfactant PVP for greatly promoted catalytic efficiency and excellent morphology, efficiency stability. In especial, sole addition of PVP not only stabilized the nanosheet morphology, also tripled the original TiO2 (B) efficiency, while TiO2 -Au-4h(PVP) displayed the highest QE of 30.9 %, and best stability. This work developed an excellent stable TiO2 (B) nanosheet based catalyst, also established a possible strategy to settle photocorrosion for other nanosheet mateials under illuminated applications. Graphical abstract: Active Au and PVP modified TiO2 (B) showed excellent morphology, efficiency stability and greatly promoted hydrogen generation. Thereinto, Au helped to transfer photo-produced electrons to proton, while PVP linked to nanosheets effectively reduced their surface energy, and protected nanosheets from restacking. Image, graphical abstract